Heat Flux at the Surface of Metal Foil Heater under Evaporating Sessile Droplets - Igor Marchuk; Andrey Karchevsky; Anton Surtaev; Oleg Kabov (International Journal of Aerospace Engineering)
Evaporating water drops on a horizontal heated substrate were investigated experimentally. The heater was made of a constantan foil with the thickness of 25 μm and size of 42 × 35 mm2. The temperature of the bottom foil surface was measured by the infrared (IR) camera. To determine the heat flux density during evaporation of liquid near the contact line, the Cauchy problem for the heat equation was solved using the temperature data. The maximum heat flux density is obtained in the contact line region and exceeds the average heat flux density from the entire foil surface by the factor of 5–7. The average heat flux density in the region wetted by the drop exceeds the average heat flux density from the entire foil surface by the factor of 3–5. This fact is explained by the heat influx from the foil periphery to the drop due to the relatively high heat conductivity coefficient of the foil material and high evaporation rate in the contact line region. Heat flux density profiles for pairs of sessile droplets are also investigated.